A HDI circuit board substrate material and preparation method thereof
By preparing a modified insulating film, an acid anhydride is generated by the oxidation reaction of 3,4-dimethylthiophenyl and benzene, and is imidized with ethylenediaminetetraacetic dianhydride and tris(2-aminoethyl)amide imidized with ethylenediaminetetraacetic dianhydride and tris(2-aminoethyl)amide imidized Polymerization, combined with reinforced fillers, solves the problems of heat resistance and bonding strength of the inner core plate material of HDI board, and achieves efficient insulation and mechanical properties of HDI board substrate material.
Patent Information
- Application Number
- CN202211207373.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The inner core board materials of existing HDI boards have poor heat resistance and low strength, making them difficult to apply under high power conditions. The high melting point of polyimide resin makes processing difficult and combined with copper foil. Low intensity increases production difficulty and affects miniaturization.
Modified insulating film is heated and stirred by 3,4-dimethylthiophenyl and benzene and then added with potassium permanganate solution for oxidation to form an acid anhydride containing disulfide, followed by dianhydride and tris( 2-aminoethyl)amine imidized polymerization prepares polyimide resins with excellent insulation properties, and enhances the film by strengthening the porous structure made of fillers such as amino silicone oil and octamethylcyclotetrasiloxane. mechanical properties.
It realizes HDI board substrate material with excellent insulation performance and high bonding strength under high temperature environments, reduces the glass transition temperature, facilitates hot processing and recycling processing, and improves the mechanical properties of the film and the bonding strength of the copper foil.
Smart Images

Figure GDA0003920511190000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of HDI circuit boards, and in particular, relates to an HDI circuit board substrate material and a preparation method thereof. Background Art
[0002] HDI board is a circuit board with a relatively high line distribution density using micro blind buried hole technology. It is composed of an inner core board and a build-up layer. Circuits are arranged on the inner core board and the build-up layer. Through holes are formed between the layers by drilling and hole metallization, and then internal connectivity is achieved through the through holes between the layers.
[0003] The inner core board is the skeleton of the circuit board, which is made of insulating material and copper-clad on both sides. In the prior art, epoxy resin is commonly used as the insulating material of the inner core board. Due to the poor heat resistance and low strength of epoxy resin, it is difficult to be used under high-power conditions. Therefore, polyimide resin-based core board materials have been developed in the prior art to replace epoxy resin for use in high-power boards. However, the high melting point of polyimide makes the processing of the core board difficult. Due to the low bonding strength between the hardened polyimide resin and the copper foil, adhesives are generally used for bonding the copper cladding on the surface, which increases the difficulty of production. Due to the presence of the adhesive, the thickness of the inner core board is increased, or the thickness of the inner insulating layer is reduced, which is not conducive to the miniaturization of the HDI board. Summary of the invention
[0004] In order to solve the technical problems in the background technology, the object of the present invention is to provide a HDI circuit board substrate material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An HDI circuit board substrate material, comprising a modified insulating film and copper foil hot-pressed on both sides of the modified insulating film;
[0007] The modified insulating film is prepared by the following steps:
[0008] Step A1: 3,4-dimethylthiophenol and benzene are heated and stirred to mix, and then potassium permanganate solution is added and stirred at high speed. The methyl group and the thiol group on the benzene ring are oxidized by the oxidation effect of potassium permanganate, and then vacuum rotary evaporation is performed. Then, a small amount of phosphorus pentoxide is slowly added under stirring to further oxidize and dehydrate the oxidation product, and the filtrate is filtered while hot to obtain compound a;
[0009] Step A2: Compound a is mixed with anhydrous ethanol, and air containing ammonia is introduced into the mixed reaction liquid under heating and stirring. Under the conditions of ethanol and ammonia, the sulfonic acid groups on the benzene ring react to generate anhydride containing disulfide. After the reaction is completed, the anhydrous ethanol is removed by rotary evaporation to obtain compound b;
[0010] Step A3: DMF and xylene are mixed to prepare a solvent, compound b and ethylenediaminetetraacetic dianhydride are added to the solvent and stirred until dissolved, nitrogen is used to expel air from the reaction system and nitrogen is continuously introduced for protection, the mixed solution is heated to 95-110° C., tris(2-aminoethyl)amine is slowly added under stirring, reflux and stir to react for 20-25 minutes, and then vacuum rotary evaporation is performed to control the viscosity of the reactant after rotary evaporation to be no more than 12000 cP, to obtain a modified rubber material;
[0011] Step A4: taking the reinforcing filler and the modified rubber material and putting them into an internal mixer to mix them into a composite rubber material, then casting the composite rubber material into a film, and then curing it by hot air to obtain a modified insulating film.
[0012] Furthermore, the mass ratio of compound b, ethylenediaminetetraacetic dianhydride and tris(2-aminoethyl)amine is: 2.8-3.5:1.7-2.0:5.2-5.5.
[0013] Furthermore, the mass ratio of the reinforcing filler to the modified rubber material is 1:0.2-0.4.
[0014] The reinforcing filler is prepared by the following steps:
[0015] Step B1: Add aluminum nitrate to an ethanol solution and stir until completely dissolved, then dropwise add hydrochloric acid solution to adjust the pH value of the solution to 6 to prepare a solution;
[0016] Step B2: Add AEO3, amino silicone oil, octamethylcyclotetrasiloxane and triethyl borate to the dissolved solution and stir at high speed to form an emulsion;
[0017] Step B3: heating the emulsion to 60° C., adding sodium hydroxide solution dropwise while stirring until the pH value of the reaction solution reaches 8.5, stirring the reaction until a gel-like substance is generated in the reaction solution, filtering out the hydrogel, and drying the hydrogel to constant weight to obtain a composite gel;
[0018] Step B4: The composite gel is put into a pulverizer and crushed into small particles, and then added to a ball mill for wet grinding. The ball milled slurry is filtered and dried, and then put into an oxidation furnace for sintering at 820°C for 30 minutes. After being taken out, it is put into a high-speed pulverizer for crushing to make a reinforcing filler.
[0019] Furthermore, the mass ratio of aluminum nitrate, amino silicone oil, octamethylcyclotetrasiloxane and triethyl borate is 2-5:5-10:20-30:1-5.
[0020] Furthermore, the mode particle size of the particles in the ball mill slurry is 0.5-2 μm.
[0021] Furthermore, the median particle size of the reinforcing filler is 5-10 μm.
[0022] A method for preparing a HDI circuit board substrate material comprises the following steps:
[0023] Step S1: cutting the copper foil and the modified insulating film, and washing the cut copper foil with alkali to remove oil, acid to remove the oxide layer, and then vacuum drying after rinsing;
[0024] Step S2: Take the treated copper foil and cover both sides of the modified insulating film, then put it into a vacuum pressing machine to press the copper foil and the modified insulating film into shape, so as to obtain the HDI circuit board substrate material.
[0025] Furthermore, the temperature of the pressing molding is 190-210° C., the pressure of the pressing molding is 1.2-1.5 MPa, and the holding time of the pressing molding is 8-15 s.
[0026] Beneficial effects of the present invention:
[0027] 1. The present invention provides a modified adhesive material, which is a polyimide resin prepared by imidization polymerization of compound b, ethylenediaminetetraacetic acid dianhydride and tris(2-aminoethyl)amine, and has excellent insulation properties and is suitable for the substrate of HDI board;
[0028] Compound b is prepared from compound a by oxidation and dehydration of 3,4-dimethylthiophenol. Compound a generates compound b under ethanol and ammonia conditions. Compound b is an anhydride of disulfide. After polymerization, the main chain contains a thioether bond. The glass transition temperature of the modified adhesive is reduced by introducing the thioether bond and copolymerizing ethylenediaminetetraacetic acid dianhydride. Compared with the existing epoxy resin-based substrate, the glass transition temperature is higher and can be used in a higher temperature environment. Compared with the existing polyimide resin substrate, the glass transition temperature is lower and is convenient for thermal processing and recycling.
[0029] The modified adhesive contains a large amount of sulfur in its molecular chain, which has a strong coordination effect with copper, making the modified adhesive and copper foil have excellent bonding strength. After testing, the peel strength reaches 16.5-18.4N / cm.
[0030] 2. The present invention adopts a reinforcing filler and a modified adhesive material to blend into a modified insulating film, wherein the reinforcing filler is prepared into a gel by liquid hydrolysis of amino silicone oil and octamethylcyclotetrasiloxane, and aluminum and boron are uniformly dispersed. The gel is dried and ball-milled into fine particles, and the fine particles are sintered and then crushed, so that the reinforcing filler has a porous structure, and the bonding area between the reinforcing filler and the modified adhesive material is increased, thereby increasing the bonding strength between the modified adhesive material and the reinforcing filler, so that the modified insulating film has good mechanical properties. The reinforcing filler is essentially a mixed oxide of silicon, aluminum and boron, has a low dielectric constant, and is suitable for the substrate of the HDI board. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment prepares a reinforced filler, and the specific implementation process is as follows:
[0034] Step B1: Take 100g of aluminum nitrate and put it into a stirrer, add 50% ethanol solution by mass and stir until the aluminum nitrate is completely dissolved, add hydrochloric acid solution dropwise and stir to mix, adjust the pH value of the solution to 6, and prepare a dissolving solution;
[0035] Step B2: Add 20 g AEO3, 500 g amino silicone oil (nominal molecular weight of 2000, ammonia value of 0.5 mmol / g), 1 kg octamethylcyclotetrasiloxane and 250 g triethyl borate to the dissolved solution, control the stirring rate to 3000 rpm and stir at high speed for 5 min to prepare an emulsion;
[0036] Step B3: The emulsion was heated to 60°C, and sodium hydroxide solution was slowly added dropwise while stirring at 180 rpm to make the pH value 8.5, and the reaction was stirred until a gel-like substance was generated in the reaction solution, and the hydrogel was filtered out. The hydrogel was placed in a drying oven and dried to constant weight under hot air at 120°C to obtain a composite gel;
[0037] Step B4: Put the composite gel into a pulverizer and crush it into small particles. Then add it to a ball mill for cyclic wet grinding until the mode particle size of the particles in the ball mill slurry is about 0.5μm. Take out the ball mill slurry for filtration. After the filter cake is dried, put it into an oxidation furnace, heat it to 820℃ and sinter it for 30min. After taking it out, put it into a high-speed pulverizer for crushing until the median particle size of the crushed material is about 5μm to make a reinforcing filler.
[0038] Example 2
[0039] This embodiment prepares a reinforced filler, and the specific implementation process is as follows:
[0040] Step B1: Take 250g of aluminum nitrate and put it into a stirrer, add 50% ethanol solution by mass and stir until the aluminum nitrate is completely dissolved, add hydrochloric acid solution dropwise and stir to mix, adjust the pH value of the solution to 6, and prepare a dissolving solution;
[0041] Step B2: Add 30 g AEO3, 250 g amino silicone oil (nominal molecular weight of 2000, ammonia value of 0.5 mmol / g), 1.5 kg octamethylcyclotetrasiloxane and 50 g triethyl borate to the dissolved solution, control the stirring rate to 3000 rpm and stir at high speed for 10 min to prepare an emulsion;
[0042] Step B3: The emulsion was heated to 60°C, and sodium hydroxide solution was slowly added dropwise while stirring at 180 rpm to make the pH value 8.5, and the reaction was stirred until a gel-like substance was generated in the reaction solution, and the hydrogel was filtered out. The hydrogel was placed in a drying oven and dried to constant weight under hot air at 120°C to obtain a composite gel;
[0043] Step B4: Put the composite gel into a pulverizer and crush it into small particles. Then add it to a ball mill for cyclic wet grinding until the mode particle size of the particles in the ball mill slurry is about 2μm. Take out the ball mill slurry for filtration. After the filter cake is dried, put it into an oxidation furnace, heat it to 820℃ and sinter it for 30min. After taking it out, put it into a high-speed pulverizer for crushing until the median particle size of the crushed material is about 10μm to make a reinforcing filler.
[0044] Example 2
[0045] This embodiment prepares a reinforced filler, and the specific implementation process is as follows:
[0046] Step B1: 150 g of aluminum nitrate is placed in a stirrer, and a 50% by mass ethanol solution is added and stirred until the aluminum nitrate is completely dissolved, and a hydrochloric acid solution is added dropwise and stirred to mix, and the pH value of the solution is adjusted to 6 to prepare a dissolving solution;
[0047] Step B2: Add 25 g AEO3, 420 g amino silicone oil (nominal molecular weight of 2000, ammonia value of 0.5 mmol / g), 1.2 kg octamethylcyclotetrasiloxane and 170 g triethyl borate to the dissolved solution, control the stirring rate to 3000 rpm and stir at high speed for 16 min to prepare an emulsion;
[0048] Step B3: The emulsion was heated to 60°C, and sodium hydroxide solution was slowly added dropwise while stirring at 180 rpm to make the pH value 8.5, and the reaction was stirred until a gel-like substance was generated in the reaction solution, and the hydrogel was filtered out. The hydrogel was placed in a drying oven and dried to constant weight under hot air at 120°C to obtain a composite gel;
[0049] Step B4: The composite gel is placed in a pulverizer and crushed into small particles, and then added to a ball mill for cyclic wet grinding until the mode particle size of the particles in the ball mill slurry is about 1 μm. The ball mill slurry is taken out for filtration, and the filter cake is dried and placed in an oxidation furnace, heated to 820°C and sintered for 30 minutes. After being taken out, it is placed in a high-speed pulverizer for crushing until the median particle size of the crushed material is about 8 μm to prepare a reinforcing filler.
[0050] Example 4
[0051] This embodiment prepares a modified insulating film, and the specific implementation process is as follows:
[0052] Step A1: 60g 3,4-dimethylthiophenol and 500mL benzene are added to a stirrer, stirred and heated to 50°C to mix the two, and 50mL saturated potassium permanganate solution (room temperature) is poured into the mixed solution, stirred at high speed at 1000rpm for 20min, and then reduced to -0.1MPa. The temperature is raised to 80°C and rotary evaporated for 10min. After the reduced pressure rotary evaporated, the speed is controlled to 360rpm, and 12g phosphorus pentoxide is slowly sprinkled in, filtered while hot, and the filtrate is taken to obtain compound a;
[0053] Step A2: Compound a and 3 times its mass of anhydrous ethanol were mixed and dissolved, the temperature was raised to 55°C, the stirring rate was controlled to 300 rpm, and air containing 30% ammonia was introduced into the mixed solution at a rate of 4.5 L / L for 1 h. After the introduction, the vacuum rotary evaporation was performed for 30 min with the same parameters as in step A1 to obtain compound b;
[0054] Step A3: DMF and xylene were mixed in a volume ratio of 2:1 to prepare a solvent, 56 g of compound b and 40 g of ethylenediaminetetraacetic dianhydride were added to a reactor, the solvent was added and stirred until dissolved, nitrogen was introduced into the reactor to expel the air in the reaction system and nitrogen was continuously introduced for protection, the mixed solution was heated to 95°C, 104 g of tris(2-aminoethyl)amine was added dropwise under stirring, the dropping time was controlled to be 40 min, after the dropping was completed, the mixture was refluxed and stirred for 20 min, and then the reduced pressure rotary evaporation was continued, and the viscosity of the reactant after rotary evaporation was controlled to be 12000 cP, to obtain a modified rubber material;
[0055] Step A4: Take 200 g of the modified rubber material and 1 kg of the reinforcing filler prepared in Example 1, add them into an internal mixer, mix them at 60°C for 15 minutes to obtain a composite rubber material, then put the composite rubber material into a casting machine, and cast it into a casting film with a thickness of 0.2 mm. After that, cure it in a tunnel drying box at 60°C for 30 minutes to make a modified insulating film.
[0056] Example 5
[0057] This embodiment prepares a modified insulating film, and the specific implementation process is as follows:
[0058] Step A1: 60g 3,4-dimethylthiophenol and 500mL benzene are added to a stirrer, stirred and heated to 50°C to mix the two, and 50mL saturated potassium permanganate solution (room temperature) is poured into the mixed solution, stirred at high speed at 1000rpm for 20min, and then reduced to -0.1MPa. The temperature is raised to 80°C and rotary evaporated for 10min. After the reduced pressure rotary evaporated, the speed is controlled to 360rpm, and 12g phosphorus pentoxide is slowly sprinkled in, filtered while hot, and the filtrate is taken to obtain compound a;
[0059] Step A2: Compound a and 3 times its mass of anhydrous ethanol were mixed and dissolved, the temperature was raised to 55°C, the stirring rate was controlled to 300 rpm, and air containing 30% ammonia was introduced into the mixed solution at a rate of 4.5 L / L for 1 h. After the introduction, the vacuum rotary evaporation was performed for 30 min with the same parameters as in step A1 to obtain compound b;
[0060] Step A3: DMF and xylene were mixed in a volume ratio of 2:1 to prepare a solvent, 60 g of compound b and 38 g of ethylenediaminetetraacetic dianhydride were added to a reactor, the solvent was added and stirred until dissolved, nitrogen was introduced into the reactor to expel the air in the reaction system and nitrogen was continuously introduced for protection, the mixed solution was heated to 100°C, 106 g of tri(2-aminoethyl)amine was added dropwise under stirring, the dropping time was controlled to be 50 min, after the dropping was completed, the mixture was refluxed and stirred for 25 min, and then the reduced pressure rotary evaporation was continued, and the viscosity of the reactant after rotary evaporation was controlled to be 12000 cP, to obtain a modified rubber material;
[0061] Step A4: Take 330g of the modified rubber material and 1kg of the reinforcing filler prepared in Example 2, add them into an internal mixer, mix them at 60°C for 15min to obtain a composite rubber material, then put the composite rubber material into a casting machine, and cast it into a casting film with a thickness of 0.2mm. After that, cure it in a tunnel drying box at 60°C for 25min to make a modified insulating film.
[0062] Example 6
[0063] This embodiment prepares a modified insulating film, and the specific implementation process is as follows:
[0064] Step A1: 60g 3,4-dimethylthiophenol and 500mL benzene are added to a stirrer, stirred and heated to 50°C to mix the two, and 50mL saturated potassium permanganate solution (room temperature) is poured into the mixed solution, stirred at high speed at 1000rpm for 20min, and then reduced to -0.1MPa. The temperature is raised to 80°C and rotary evaporated for 10min. After the reduced pressure rotary evaporated, the speed is controlled to 360rpm, and 12g phosphorus pentoxide is slowly sprinkled in, filtered while hot, and the filtrate is taken to obtain compound a;
[0065] Step A2: Compound a and 3 times its mass of anhydrous ethanol were mixed and dissolved, the temperature was raised to 55°C, the stirring rate was controlled to 300 rpm, and air containing 30% ammonia was introduced into the mixed solution at a rate of 4.5 L / L for 1 h. After the introduction, the vacuum rotary evaporation was performed for 30 min with the same parameters as in step A1 to obtain compound b;
[0066] Step A3: DMF and xylene were mixed in a volume ratio of 2:1 to prepare a solvent, 70 g of compound b and 34 g of ethylenediaminetetraacetic dianhydride were added to a reactor, the solvent was added and stirred until dissolved, nitrogen was introduced into the reactor to expel the air in the reaction system and nitrogen was continuously introduced for protection, the mixed solution was heated to 110°C, 114 g of tri(2-aminoethyl)amine was added dropwise under stirring, the dropping time was controlled to be 50 min, after the dropping was completed, the mixture was refluxed and stirred for 25 min, and then the reduced pressure rotary evaporation was continued, and the viscosity of the reactant after rotary evaporation was controlled to be 12000 cP, to obtain a modified rubber material;
[0067] Step A4: Take 400g of the modified rubber material and 1kg of the reinforcing filler prepared in Example 2, add them into an internal mixer, mix them at 60°C for 22min to obtain a composite rubber material, then put the composite rubber material into a casting machine, cast it into a casting film with a thickness of 0.2mm, and then cure it in a tunnel drying oven at 60°C for 20min to make a modified insulating film.
[0068] Example 7
[0069] In this embodiment, HDI circuit board substrate material is prepared, and the specific implementation process is as follows:
[0070] Step S1: Take a 35 μm thick copper foil for circuit boards and the modified insulating film of Example 4, cut them into sheets of 500*500 mm, soak the copper foil in 10% sodium carbonate lye for 3 min, then soak it in 5% sulfuric acid solution for 10 min, rinse it and vacuum dry it;
[0071] Step S2: Take the treated copper foil and cover both sides of the modified insulating film, then put it into a vacuum pressing machine, set the temperature to 190°C, the pressure to 1.2MPa, and the pressing time to 15s, press the copper foil and the modified insulating film into one, and obtain the HDI circuit board substrate material.
[0072] Example 8
[0073] In this embodiment, HDI circuit board substrate material is prepared, and the specific implementation process is as follows:
[0074] Step S1: Take a 35 μm thick copper foil for circuit boards and the modified insulating film of Example 5, cut them into sheets of 500*500 mm, soak the copper foil in 10% sodium carbonate lye for 3 min, then soak it in 5% sulfuric acid solution for 10 min, rinse it and vacuum dry it;
[0075] Step S2: Take the treated copper foil and cover both sides of the modified insulating film, then put it into a vacuum pressing machine, set the temperature to 200°C, the pressure to 1.3MPa, and the pressing time to 13s, press the copper foil and the modified insulating film into one, and obtain the HDI circuit board substrate material.
[0076] Example 9
[0077] In this embodiment, HDI circuit board substrate material is prepared, and the specific implementation process is as follows:
[0078] Step S1: Take a 35 μm thick copper foil for circuit boards and the modified insulating film of Example 6, cut them into sheets of 500*500 mm, soak the copper foil in 10% sodium carbonate lye for 3 min, then soak it in 5% sulfuric acid solution for 10 min, rinse it and vacuum dry it;
[0079] Step S2: Take the treated copper foil and cover both sides of the modified insulating film, then put it into a vacuum pressing machine, set the temperature to 210°C, the pressure to 1.5MPa, and the pressing time to 8s, press the copper foil and the modified insulating film into one, and obtain the HDI circuit board substrate material.
[0080] The modified insulating films prepared in Examples 4 to 6 were tested for performance, and the specific test standards are as follows:
[0081] The glass transition temperature of the adhesive was measured by using a differential scanning calorimeter in a nitrogen atmosphere with a heating rate of 10°C / min.
[0082] Refer to GB / T1408.1-2006 to test the dielectric constant and surface resistivity of the samples;
[0083] Refer to GB / T 9534-1988 for dielectric loss test;
[0084] Flexural strength test according to ISO 178;
[0085] Notched impact strength test according to ISO 180;
[0086] The specific test data is shown in Table 1:
[0087] Table 1
[0088]
[0089] It can be seen from the data in Table 1 that the glass transition temperature of the modified insulating film prepared by the present invention is about 190°C. Compared with the existing epoxy resin-based substrate, the glass transition temperature is higher and can be used in a higher temperature environment. Compared with the existing polyimide resin substrate, the glass transition temperature is lower, which is convenient for thermal processing and recycling. The modified insulating film has good processability. In addition, the modified insulating film has a low dielectric constant, low dielectric loss, and high surface resistivity, has good insulation properties, and has high impact strength and bending strength, and is suitable for substrates with HDI boards.
[0090] The HDI circuit board substrate materials prepared in Examples 7 to 9 were subjected to peeling tests, and the specific tests were as follows:
[0091] Refer to GB / T 4722-2017 for copper foil peel strength test;
[0092] The specific test data is shown in Table 2:
[0093] Table 2
[0094] Example 7 Example 8 Example 9 <![CDATA[Peeling strength / N·cm -1 > 18.4 17.9 16.5
[0095] From the data in Table 2, it can be seen that the bonding strength of the copper foil and the modified insulating film after hot pressing reaches 16.5-18.4N / cm, which has excellent bonding strength.
[0096] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0097] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A HDI circuit board substrate material, characterized in that: The modified insulating film is formed by hot pressing of a modified insulating film and a copper foil, and the modified insulating film is prepared by the following steps: Step A1: Mix 3,4-dimethylthiophenol and benzene, add potassium permanganate solution to mix and oxidize, add phosphorus pentoxide to dehydrate after vacuum rotary evaporation while stirring, filter while hot, and take the filtrate to prepare compound a; Step A2: Compound a is mixed with anhydrous ethanol, air containing ammonia is introduced under stirring at elevated temperature, and after the reaction is completed, the mixture is subjected to rotary evaporation to obtain compound b; Step A3: DMF and xylene are mixed to prepare a solvent, compound b and ethylenediaminetetraacetic dianhydride are added to the solvent and stirred until dissolved, tri(2-aminoethyl)amine is added under nitrogen protection and stirring, and then refluxed, heated and stirred for 20-25 minutes. After the reaction is completed, vacuum rotary evaporation is performed to control the viscosity of the reactant after rotary evaporation to be no more than 12000 cP, to obtain a modified rubber material; Step A4: taking the reinforcing filler and the modified rubber material and putting them into an internal mixer to mix them into a composite rubber material, then casting the composite rubber material into a film, and then hot-air curing it to obtain a modified insulating film; The reinforcing filler is prepared by the following steps: Step B1: adding aluminum nitrate to an ethanol solution and stirring to dissolve, and adding a hydrochloric acid solution dropwise to adjust the pH value of the solution to 6 to prepare a solution; Step B2: Add AEO3, amino silicone oil, octamethylcyclotetrasiloxane and triethyl borate to the dissolved solution and stir to form an emulsion; Step B3: heating the emulsion to 60° C., adding sodium hydroxide solution dropwise while stirring until the pH value of the reaction solution reaches 8.5, stirring to react to form a hydrogel, and drying the hydrogel to constant weight to obtain a composite gel; Step B4: The composite gel is crushed and then added to a ball mill for wet grinding. The ball mill slurry is filtered and the filter cake is dried and placed in an oxidation furnace for sintering at 820° C. for 30 minutes. After being taken out, it is crushed again to prepare a reinforcing filler.
2. The HDI circuit board substrate material according to claim 1, characterized in that: The mass ratio of compound b, ethylenediaminetetraacetic dianhydride and tris(2-aminoethyl)amine is: 2.8-3.5:1.7-2.0:5.2-5.
5.
3. The HDI circuit board substrate material according to claim 1, characterized in that: The mass ratio of the reinforcing filler to the modified rubber material is 1:0.2-0.
4.
4. The HDI circuit board substrate material according to claim 1, characterized in that: The mass ratio of aluminum nitrate, amino silicone oil, octamethylcyclotetrasiloxane and triethyl borate is 2-5:5-10:20-30:1-5.
5. The HDI circuit board substrate material according to claim 1, characterized in that: The mode particle size of the particles in the ball mill slurry is 0.5-2 μm.
6. The HDI circuit board substrate material according to claim 1, characterized in that: The median particle size of the reinforcing filler is 5-10 μm.
7. The method for preparing a HDI circuit board substrate material according to claim 1, characterized in that: The steps include: Step S1: cutting the copper foil and the modified insulating film, and washing the cut copper foil with alkali to remove oil, acid to remove the oxide layer, and then vacuum drying after rinsing; Step S2: Take the treated copper foil and cover both sides of the modified insulating film, then put it into a vacuum pressing machine to press the copper foil and the modified insulating film into shape, so as to obtain the HDI circuit board substrate material.
8. The method for preparing a HDI circuit board substrate material according to claim 7, characterized in that: The temperature of the pressing molding is 190-210°C, the pressure of the pressing molding is 1.2-1.5MPa, and the holding time of the pressing molding is 8-15s.
